2009
DOI: 10.1007/s00424-009-0717-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide modifies amiloride-sensitive Na+ transport processes across human airway cells: role of mitogen-activated protein kinases ERK 1/2 and 5

Abstract: Bacterial lipopolysaccharides (LPS) are potent inducers of proinflammatory signaling pathways via the activation of nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK), causing changes in the processes that control lung fluid homeostasis and contributing to the pathogenesis of lung disease. In human H441 airway epithelial cells, incubation of cells with 15 µg ml−1 LPS caused a significant reduction in amiloride-sensitive Isc from 15 ± 2 to 8 ± 2 µA cm−2 (p = 0.01, n = 13) and a shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Numerous previous studies have reported that ENaC may be regulated by LPS; however, these findings are discrepant, as both increases and decreases in expression were observed (10,11). Moreover, it has also been reported that ENaC expression was not affected by LPS induction (9,12).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Numerous previous studies have reported that ENaC may be regulated by LPS; however, these findings are discrepant, as both increases and decreases in expression were observed (10,11). Moreover, it has also been reported that ENaC expression was not affected by LPS induction (9,12).…”
Section: Discussionmentioning
confidence: 87%
“…LPS has been demonstrated to modify Na + transport in the airway epithelium by regulating either ENaC mRNA expression (8) or the ENaC channel current (9). The effect of LPS on α-ENaC expression in rats and airway cell lines is controversial, as expression has been observed to increase and decrease (10,11), and in certain studies, to remain unchanged following LPS induction (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinical investigations have revealed a positive correlation between mortality and levels of circulating TNF-α, IL-1β, IL-6 and IL-8 in ALI (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In the present study, the reduction in inflammatory cytokine levels observed in the plasma of ALI rats following PNS treatment may have contributed to a reduction in leukocyte adhesion and infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…OA has been reported to inhibit alveolar fluid reabsorption (24) and the endotoxin, LPS, has been indicated to adversely affect ENaC-mediated Na + transport (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation